1997
DOI: 10.1063/1.119862
|View full text |Cite
|
Sign up to set email alerts
|

Efficient route to TlBa2Ca2Cu3O9+x thin films by metal-organic chemical vapor deposition using TlF as a thallination source

Abstract: Thin TlBa2Ca2Cu3O9+x films were grown on single crystal (110) LaAlO3 from metal-organic chemical-vapor deposition-derived Ba–Ca–Cu–Ox precursor films employing Ba(hfa)2⋅mep, Ca(hfa)2⋅tet, and Cu(dpm)2 (hfa=hexafluoroacetylacetonate; dpm=dipivaloylmethanate; tet=tetraglyme; mep=methylethylpentaglyme) as the volatile metal sources. Thallination is then accomplished by annealing the precursor films in the presence of a bulk BaO+CaO+CuO+TlF source at 885 °C in flowing O2. The presence of TlF is essential for nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A low magnification view of the t q ‫ס‬ 540 min specimen indicates a thin film lacking the multiple random orientations seen at earlier stages; however, significant strain at the substrate-superconductor interface is also evident. In our previous report, 6 we observed several layers of Tl-1212 and a mixed-phase region between the LAO/ TBCCO interface and the phase-pure Tl-1223. 14(a) are amorphous grains of Ba-Cu-O corresponding to the surface impurities observed in the SEM pictures.…”
Section: Tem Observationsmentioning
confidence: 55%
See 1 more Smart Citation
“…A low magnification view of the t q ‫ס‬ 540 min specimen indicates a thin film lacking the multiple random orientations seen at earlier stages; however, significant strain at the substrate-superconductor interface is also evident. In our previous report, 6 we observed several layers of Tl-1212 and a mixed-phase region between the LAO/ TBCCO interface and the phase-pure Tl-1223. 14(a) are amorphous grains of Ba-Cu-O corresponding to the surface impurities observed in the SEM pictures.…”
Section: Tem Observationsmentioning
confidence: 55%
“…3 Long-length, coated conductors employing Tl-1223 also lie within the realm of possibility, as has been illustrated by (Tl,Bi)-1223 growth on CeO 2 -buffered, single-crystal yttria-stabilized zirconia (YSZ) and on multibuffered rolling-assisted biaxially textured Ni substrates. 6 Such films are epitaxial, display excellent alignment with the (110) LaAlO 3 substrates, and exhibit T c ‫ס‬ 103 K and J c > 10 5 A/cm 2 at 5 K as determined by magnetic measurements in fields up to 4.5 T. Compared with the unsubstituted Tl-1223 thin films of other groups, 7,8 films annealed in the presence of T1F produce Tl-1223 at a considerably lower temperature. Recently, we reported phase-selective nucleation of metal-unsubstituted Tl-1223 thin films from metalorganic chemical vapor deposition (MOCVD) derived BaCaCuO(F) precursor films that were postannealed at 885°C in the presence of TlF as opposed to commonly employed Tl 2 O 3 .…”
mentioning
confidence: 94%
“…[88] in the starting composition of Tl-1223 enhances the formation of single phase Tl-1223 material with out any Pb or Srdoping and increases J c (77K, 0T) and irreversibility field H irr [90,91]. The thin films of Tl-1223 prepared by using TlF are found to have critical current density of 4.410 6 A/cm 2 at 77K in zero field [84]. Since the ionic radius of fluorine [F -1 (1.36Å)] is comparable to that of oxygen [O -2 (1.4 Å)] so fluorine most probably occupies the oxygen lattice site in the unit cell [92].…”
Section: Tl 1 Ba 2 Ca N-1 Cu N O 2n+2 Superconductorsmentioning
confidence: 99%
“…In the preparation of Tl-1223 compounds it is found that a starting composition deficient in thallium produces the highest percentage of Tl-1223 phase [8]. The high vapor pressure of Tl 2 O 3 at synthesis temperatures also hinders the formation of Tl-1223 superconductors [84,85]. This problem can be overcome by employing the two zone processing technique in which independent control of partial pressure of Tl 2 O 3 , oxygen gas, sample temperature and composition could be varied [68,85,86].…”
Section: Tl 1 Ba 2 Ca N-1 Cu N O 2n+2 Superconductorsmentioning
confidence: 99%
See 1 more Smart Citation